Phytochemical screening and evaluation of antioxidant and antibacterial activities of seeds and pods extracts of Calycotome villosa subsp. Intermedia - Aouicha Elkhamlichia, Hanane El Hajajia, Hassan Farajb, Anouar Alamib, Brahim El Balia, Mohammed Lachkara (Journal of Applied Pharmaceutical Science, 2017)
In the present study, antioxidant potential of the methanol and the ethyl acetate extracts of the seeds and pods of Calycotome villosa subsp. intermedia were evaluated by using 1,1-diphenyl-2-picrylhydrazyl (DPPH) scavenging assay, reducing power and total antioxidant capacity. In DPPH scavenging assay, the IC50 value of the methanolic extract of seeds was found to be 0.20 mg/mL, the standard reference value for butylatedhydroxytoluene (BHT) is 0.19 mg/mL. Total antioxidant activity was also found to increase in a dose dependent manner. Moreover, Calycotome villosa extract showed strong reducing power. The total phenolic content in the extracts was determined using Folin-Ciocalteu reagent and their amounts ranged between 173.37 ± 0.02 to 332.23 ± 0.01 mg GA (Gallic Acid)/g of dry extract. The concentrations of flavonoids in the extracts varied from 5.02 ± 0.03 to 66.45 ± 0.01 Qu (Quercetin)/g of dry extract. Ethyl acetate extract of seeds of Calycotome villosa showed the highest phenolic, flavonoids concentration and the strongest antioxidant activity. The high contents of phenolic compounds indicated that these compounds contribute to the antioxidant activity. Furthermore, all extracts showed good antibacterial activity against Escherichia coli. Calycotome villosa subsp. intermedia can be regarded as promising candidate for natural plant sources of antioxidants with high value.
Keywords: Calycotome villosa subsp. intermedia, antioxidant activity, total flavonoids contents, total phenolic contents, antibacterial activity.